MODEL EVALUASI SIARAN RADIO EDUKASI DARI RADIO MITRA HINGGA PENDENGAR - Innayah Innayah (Jurnal Kependidikan, 2014)
This study is aimed to find out the significance of a radio broadcasting evaluation, the method of educational radio broadcasting, and the strategy of broadcasting evaluation for radio partner of BPMRP Pustekkom (The Center of Communication Technology) of the Ministry of Education and Cultures. This study uses a descriptive analysis. The evaluation is carried out to understand the development of the broadcasting, to identify its audience categories, to monitor the audiences, to take the audience data, to meet to audiences, and to survey the audiences. The study shows that the evaluation of radio broadcasting is of important to carry out in order to re-examine a program proposal that is already arranged beforehand. The evaluation is also important to find out the success and the failure of a program.